Reconstructing the Role of The State in Islamic Economics Based On Maqashid Al-Shariah: A Critical Analysis Of Indonesia’s Economic Policies - Khatimah, Husnul; Rudiyanto, Rudiyanto (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2025)
The role of the state in Islamic economics extends beyond market regulation and macroeconomic stability. From the perspective of maqasid al-shariah, the state bears a normative responsibility to ensure distributive justice, social welfare, and sustainable development. However, economic policies in many Muslim-majority countries, including Indonesia, remain largely influenced by conventional paradigms that prioritize growth and efficiency over substantive welfare outcomes. This study critically examines the gap between the ideal role of the state in Islamic economics and its implementation in Indonesia’s economic policies. Employing a qualitative library research approach, this study analyzes classical and contemporary Islamic economic literature, recent reputable journal articles, and relevant policy documents. The analysis is grounded in maqasid al-shariah, encompassing the protection of religion, life, intellect, progeny, and wealth, which are used as evaluative criteria for public policy. The findings indicate that although Indonesia has institutionalized various Islamic economic instruments—such as zakat management, waqf development, and the halal industry—these initiatives remain fragmented and largely formalistic. Maqasid al-shariah has not been fully integrated as a comprehensive framework for evaluating policy outcomes, resulting in persistent challenges such as inequality, structural poverty, and environmental degradation. This study contributes theoretically by repositioning maqasid al-shariah as a policy evaluation framework rather than merely a normative or ethical reference. Practically, it suggests that integrating maqasid-based principles into fiscal policy, market regulation, social protection, education, and sustainable development can enhance the role of the state in achieving holistic welfare in Indonesia.